2003
DOI: 10.1111/j.1572-0241.2003.08727.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Imaging Features of Autoimmune Pancreatitis With Focal Pancreatic Swelling Or Mass Formation: Comparison With So-Called Tumor-Forming Pancreatitis and Pancreatic Carcinoma

Abstract: Focal AIP is associated with clinical and radiologic features that are different from those of alcohol-induced TFP. In TFP there are two causative factors, namely, AIP and alcohol-induced chronic pancreatitis. Differential diagnosis of focal AIP from Pca seems to be possible in many cases by evaluating imaging findings such as dynamic CT and ERCP, although focal AIP sometimes shows clinical and radiologic features similar to those of Pca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
1
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(79 citation statements)
references
References 24 publications
1
69
1
8
Order By: Relevance
“…ERCP findings that differentiate AIP from pancreatic cancer include a longer stenosis in the MPD (more than 3 cm), the presence of branches in the stenosed MPD region, and, after a stenosis of less than 4 mm, a non-dilated MPD [100,101]. These findings are not possible to discern in cases with MPD obstruction.…”
Section: (Level Of Recommendation: B)mentioning
confidence: 49%
“…ERCP findings that differentiate AIP from pancreatic cancer include a longer stenosis in the MPD (more than 3 cm), the presence of branches in the stenosed MPD region, and, after a stenosis of less than 4 mm, a non-dilated MPD [100,101]. These findings are not possible to discern in cases with MPD obstruction.…”
Section: (Level Of Recommendation: B)mentioning
confidence: 49%
“…2 Previous studies investigated the recurrence of AIP, but they reported lower recurrence rates, ranging from 6 to 23 %. [5][6][7] Though the exact reasons for these discrepancies are unclear, they may be related to the number of patients, the follow-up periods, and the type of corticosteroid therapy may be related.…”
Section: Outcome Recurrence and Pancreatic Stone Formationmentioning
confidence: 99%
“…Because there is no gold standard for the diagnosis of AIP, the differentiation from pancreatic cancer can be difficult (7)(8)(9)(10)(11). On the other hand, few previous reports have described pancreatic cancer associated with AIP (12).…”
Section: Recently There Have Been Many Reports Supporting the Hypothmentioning
confidence: 99%